2017
DOI: 10.1002/adsc.201601406
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective, Isomerization‐Free Synthesis of N‐Acylketimines from N–H Imines

Abstract: N‐Acylketimines were synthesized through a ruthenium‐catalyzed generation of N–H ketimines from secondary azides and subsequent acylation with mixed anhydrides under mild conditions. The synthetic scope was broad to give N‐acylimines having various functional groups, including those with aliphatic groups that are prone to tautomerization to the corresponding enamides. In addition, various acyl moieties were accommodated. The synthetic utility of this chemoselective imine generation was illustrated by a highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…In addition, there is no efficient synthetic method to access stereochemically pure N -acyl ketimine. One study reported an isomerization-free method to access N -acyl imines from hazardous secondary azides under light irradiation, but the compatibility of this method for the synthesis of α-alkylated ketimines with large steric hindrance was not demonstrated.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, there is no efficient synthetic method to access stereochemically pure N -acyl ketimine. One study reported an isomerization-free method to access N -acyl imines from hazardous secondary azides under light irradiation, but the compatibility of this method for the synthesis of α-alkylated ketimines with large steric hindrance was not demonstrated.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, we were unable to find a set of conditions that provided detectable amounts of desired macrocycle 44 . We also attempted to close the macrocycle with an intramolecular Mannich reaction using photochemistry to generate the requisite imine . Azide 45 was transformed to imine smoothly by a ruthenium catalyst, followed by in situ acylation-delivered N -acylimine 46 in one pot.…”
Section: Approaches Toward Lankacidin C and 4-methyl Lankacidin Cmentioning
confidence: 99%
“…We were able to successfully affect ring closure on a derivative with an extra methyl group at C4 (resulting in a quaternary center), supporting the hypothesis that the β-keto-δ-lactone motif decomposes via β-elimination . We next screened a Mannich approach for macrocycle formation by means of photochemical imine formation (Scheme B) . Azide 129 , generated with a Mitsunobu reaction, was transformed into the imine in the presence of a ruthenium catalyst and light, followed by in situ acylation delivered N -acylimine 130 in one pot.…”
Section: Modular Approaches To Lankacidin Antibioticsmentioning
confidence: 62%